Sentence-Based Attentional Mechanisms in Word Learning: Evidence from a Computational Model - Alishahi, Afra; Fazly, Afsaneh; Koehne, Judith; Crocker, Matthew W. (Frontiers in Psychology, 2012)
When looking for the referents of nouns, adults and young children are sensitive to cross- situational statistics (Yu & Smith, 2007; Smith & Yu, 2008). In addition, the linguistic context that a word appears in has been shown to act as a powerful attention mechanism for guiding sentence processing and word learning (Landau & Gleitman, 1985; Altmann & Kamide, 1999; Kako & Trueswell, 2000). Koehne & Crocker (2010, 2011) investigate the interaction between cross-situational evidence and guidance from the sentential context in an adult language learning scenario. Their studies reveal that these learning mechanisms interact in a complex manner: they can be used in a complementary way when context helps reduce referential uncertainty; they influence word learning about equally strongly when cross-situational and contextual evidence are in conflict; and contextual cues block aspects of cross-situational learning when both mechanisms are independently applicable. To address this complex pattern of findings, we present a probabilistic computational model of word learning which extends a previous cross-situational model (Fazly et al., 2010) with an attention mechanism based on sentential cues. Our model uses a framework that seamlessly combines the two sources of evidence in order to study their emerging pattern of interaction during the process of word learning. Simulations of the experiments of Koehne & Crocker (2010, 2011) reveal an overall patterns of results that are in line with their findings. Importantly, we demonstrate that our model does not need to explicitly assign priority to either source of evidence in order to produce these results: learning patterns emerge as a result of a probabilistic interaction between the two types of cues. Moreover, using a computational model allows us to examine the developmental trajectory of the differential roles of cross-situational and sentential cues in word learning.